Distinguishing Chromatic Numbers of Bipartite Graphs - Laflamme, C.; Seyffarth, K. (The Electronic Journal of Combinatorics, 2009)
Extending the work of K.L. Collins and A.N. Trenk, we characterize connected bipartite graphs with large distinguishing chromatic number. In particular, if G is a connected bipartite graph with maximum degree Δ ≥ 3, then χ_D(G)≤ 2Δ -2 whenever G otK_Δ-1,Δ, K_Δ,Δ.